Evaluation of Optic Disc, Retinal Vascular Structures, and Acircularity Index in Patients with Idiopathic Macular Telangiectasia Type 2 - Muhammet Kazim Erol; Birumut Gedik; Yigit Caglar Bozdogan; Rojbin Ekinci; Mehmet Bulut; Berna Dogan; Elcin Suren; Melih Akidan (Diagnostics, 2023)
Background: We aimed to compare the retinal, optic disc vascular density (ODVD) values, and acircularity index (AI) of patients with idiopathic macular telangiectasia type 2 (IMT) and healthy individuals using the optical coherence tomography angiography (OCTA) device. Methods: The study included 39 patients with IMT and 37 healthy controls. The OCTA findings of the patients and controls were examined. Results: The total, parafoveal and perifoveal vascular density of the superficial capillary plexus, choriocapillaris blood flow, inside-disc ODVD, retinal nerve fiber layer (RNFL), and retinal thicknesses were found to be statistically significantly lower, and the foveal avascular zone value was statistically significantly higher in the IMT group compared to the control group (p = 0.001, p = 0.01, p = 0.02, p = 0.01, p = 0.009, p = 0.002, p = 0.02, respectively). There was a statistically significant negative correlation between best-corrected visual acuity (BCVA) and AI (p = 0.02), and a statistically significant positive correlation between peripapillary vascular density and BCVA (p = 0.04). Conclusions: We consider that the lower retinal, choriocapillaris, ODVD values, and retinal and RNFL thicknesses in the patients with IMT compared to the controls were due to vascular damage, remodeling, fibrosis, proliferation, and Müller cell damage. Ellipsoid zone defect, AI, and peripapillary vascular density are important indicators in the evaluation of visual acuity in these patients.